2001
DOI: 10.1590/s0100-879x2001000500017
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent effects of diazepam and the 5-HT2B/2C receptor antagonist SB 206553 in spontaneously hypertensive and Lewis rats tested in the elevated plus-maze

Abstract: The 5-HT 2B/2C receptor antagonist SB 206553 exerts anxiolytic effects in rat models of anxiety. However, these effects have been reported for standard rat strains, thus raising the issue of SB 206553 effects in rat strains displaying different levels of anxiety. Herein, the effects of SB 206553 in a 5-min elevated plus-maze test of anxiety were compared to those of the reference anxiolytic, diazepam, in two rat strains respectively displaying high (Lewis rats) and low (spontaneously hypertensive rats, SHR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…It should be recalled that, as previously mentioned, SHR and LEW rats differ in basal anxiety levels, the former presenting least anxiety-related behavior and the latter showing most anxiety-related behavior. In this context, it is interesting to note that in our previous studies (Takahashi et al, 2001;Vendruscolo et al, 2003) using the same models and same strain of animals, but testing other anxiolytics, such as diazepam, clordiazepoxide and NKP-608, a lack of anxiolytic-like effects of these drugs was seen in the LEW strain. We suggested that the high-anxiety profile of these rats may be resistant to these drugs.…”
Section: Discussionmentioning
confidence: 88%
“…It should be recalled that, as previously mentioned, SHR and LEW rats differ in basal anxiety levels, the former presenting least anxiety-related behavior and the latter showing most anxiety-related behavior. In this context, it is interesting to note that in our previous studies (Takahashi et al, 2001;Vendruscolo et al, 2003) using the same models and same strain of animals, but testing other anxiolytics, such as diazepam, clordiazepoxide and NKP-608, a lack of anxiolytic-like effects of these drugs was seen in the LEW strain. We suggested that the high-anxiety profile of these rats may be resistant to these drugs.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, the LEW and SHR strains, which are known to differ in several behavioral tests of anxiety/emotionality [18-25], displayed similar anxiety-like responses when evaluated in the COT. All groups highly avoided the collar and the environment containing the cat odor.…”
Section: Introductionmentioning
confidence: 88%
“…These strains, however, do not differ in their activity levels in either novel or familiar environments [18-25] but pharmacological studies indicate that they respond differently to the anxiolytic effects of benzodiazepines [18,19,21]. The anxiety-related differences between LEW and SHR were found to be due to genetic effects [20,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the open arm entries were markedly increased and also the time spent in open arms was elevated in bAD rats, compared to CTRL-and SHAM rats, an indication of decreased anxiety-like behaviour. Also SHR are less fearful than normotensive rats in the elevated plus-maze test (Durand et al 1999;Takahashi et al 2001), though the performance of active avoidance tasks by SHR is thought to be influenced by a slower habituation, hyperactivity, and hyperreactivity (Scriabine et al 1989;Wultz et al 1990). Increased reactivity could be observed especially during exposure to novel stimuli (Sagvolden et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of different models of hypertension with a variety of behavioural, learning, and memory tasks additionally impedes comparison of the findings. For instance, renal hypertensive rats show anxiogenic-like behaviour in an elevated plus-maze test (Srinivasan et al 2003), while spontaneous hypertensive rats (SHR), another model of hypertension, have decreased levels of anxiety in an open-field test (Durand et al 1999) but also in an elevated plus-maze test (Durand et al 1999;Takahashi et al 2001). Furthermore, chronic hypertension evoked by aortic coarctation leads, ten months after surgery, to no impairment in spatial learning and memory when observing the rats during a repeated-acquisition water maze task (Kadish et al 2001).…”
mentioning
confidence: 99%